1989
DOI: 10.1002/adv.1989.060090306
|View full text |Cite
|
Sign up to set email alerts
|

Solid bed compaction and frictional drag during melting in a simulated plasticating extruder

Abstract: Solid bed transport has an important effect on the overall performance of a plasticating extruder. The coefjicient of friction and density are the properties of the solid bed that govern its transport in the feed section of the screw. These properties have been measured, as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Table 1 provides the means and ranges for the values of k for the nonwoven mats at the different PP and normal stress levels. The values in Table 1 includes the data for the different temperature levels and dwell [12] and Gang et al [20] for solid PP. The frictional response of the mats with no PP fibers was substantially lower than the values in the literature [7][8][9].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 provides the means and ranges for the values of k for the nonwoven mats at the different PP and normal stress levels. The values in Table 1 includes the data for the different temperature levels and dwell [12] and Gang et al [20] for solid PP. The frictional response of the mats with no PP fibers was substantially lower than the values in the literature [7][8][9].…”
Section: Resultsmentioning
confidence: 99%
“…Friction values obtained for PP by Hwang and McKelvey[12] ranged from 0.05 to 0.15 at similar normal stress and temperature ranges. Gang et al[20] found k for PP to drop to 0.017-0.021 at a higher temperature of 210 C. For solid wood, k was found to be between 0.10 and 0.13 at Representative frictional load curve for nonwoven mats at a surface temperature of 180 C, a 7.6-MPa normal load, and a 0-s dwell time.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Matching test conditions with extruder conditions is very important. The COF of a polymer will vary in some instances rapidly with small changes in temperature, pressure, and velocity as evident from the experimental work of many studies (3)(4)(5)(6)(7)(8)(9)(10). This is because the nature of the interface changes as the sample deforms and approaches (or exceeds) its melting or glass transition temperature.…”
Section: Introductionmentioning
confidence: 99%
“…As will be detailed further in the Experimental section, the apparatus used in this work consists of a rotating drum with the polymer impinged on this drum through the use of a sample chamber and plunger. Other designs used to study friction under extruder like conditions include a cylindrical chamber with a piston that applies pressure and also can measure torque while it rotates (8). an apparatus of similar geometry to the present work except a smaller diameter cylinder is used (9).…”
Section: Introductionmentioning
confidence: 99%